ANALISIS PENGEMBANGAN KARAKTER, KETERAMPILAN PROSES SAINS, DAN PENGUASAAN KONSEP SISWA PADA TOPIK KOLOID MELALUI PEMBELAJARAN INKUIRI TERBIMBING - Al Hafit Nur; Wahyu Sopandi; Iqbal Mustapha (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2016)
Abstract This study aims to obtain a model of learning that develop character values​​, science process skills, and mastery of concepts students. This study was designed with a quasi-experimental methods, to form